2021
DOI: 10.1039/d1sc00785h
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of thioamide peptides as selective inhibitors of cysteine protease cathepsin L

Abstract: Information on the effects of sidechain and backbone modification on the activity of cathepsin (Cts) L, V, K, S, and B was used to design a thioamide peptide that is inert to all Cts and selectively inhibits Cts L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 81 publications
0
18
0
Order By: Relevance
“…Using a sulfur atom as an alternative to an oxygen atom, a thioamide structure is a useful biomimetic for an amide bond in natural peptides because thioamide bonds are resistant to normal peptidases, which can cleave peptide bonds. 43 , 44 A thioamide-containing small drug, ethionamide has been utilized as an antibiotic to treat tuberculosis for over 60 years. 45…”
Section: Resultsmentioning
confidence: 99%
“…Using a sulfur atom as an alternative to an oxygen atom, a thioamide structure is a useful biomimetic for an amide bond in natural peptides because thioamide bonds are resistant to normal peptidases, which can cleave peptide bonds. 43 , 44 A thioamide-containing small drug, ethionamide has been utilized as an antibiotic to treat tuberculosis for over 60 years. 45…”
Section: Resultsmentioning
confidence: 99%
“…DAXAK sequences) has been shown to significantly impact the conformation of the stapled peptide, and the positioning of the Asp at the N-terminal end is plagued by aspartimide formation. 22 Synthesis of heptapeptide thioamide 19 was undertaken using standard SPPS protocols 29,38–41 (see ESI†) on Sieber amide resin (Scheme 5). The linear peptide 15 was first assembled, then the peptide was treated with alanine-derived thioacylating agent 16 to give peptide thioamide 17 on resin.…”
Section: Resultsmentioning
confidence: 99%
“… 168 Based on these observations, inhibitors of TMPRSS2, CTSL, and furin were identified as promising therapeutical agents for COVID-19 treatment. 169 …”
Section: Covid-19 Therapeutic Targets For Small Moleculesmentioning
confidence: 99%
“… 182 Structure-based design of CTSL inhibitors was carried out by Phan et al According to their report, good peptidyl substrates can be converted into CTSL inhibitors that are active at submicromolar concentrations by a single thioamide substitution in the peptide backbone. 169 By designing and scanning several thioamide-stabilized peptide scaffolds, they found that the peptide RS1A inhibits CTSL activity with >25-fold higher specificity compared to the other cathepsins. According to computational modeling analysis, the P1 thioamide N–H group of the peptide interacts with the His-163 catalytic triad of CTSL.…”
Section: Covid-19 Therapeutic Targets For Small Moleculesmentioning
confidence: 99%